Scottish softwood biochar for water remediation targeting selected persistent organic pollutants - Mohammad Umair Jamal; Ashleigh Fletcher; Alan Baby; Isaac Maso; Lidija Šiller (Adsorption Science & Technology)
A Scottish wood biochar sample was investigated for water remediation against persistent organic pollutants as a potential renewable material for adsorption processes. Textural characterisation gave a high surface area (588 m 2 /g) and a mix of microporous and mesoporous nature with an average pore width of 4 nm. Morphological analysis revealed a layered carbon structure and spectroscopic analysis showed the presence of oxygen and nitrogen-based functionalities alongside 80% atomic carbon. The biochar had an average point of zero charge of 7.44 ± 0.2. 3,4-Dichloroaniline kinetic rates were rapid (<5 min), restricting kinetic analysis, while a pseudo-second-order kinetic model was best suited to represent the kinetic data for acetaminophen and carbamazepine, suggesting chemical control. The adsorption equilibria were most appropriately described by the Sips isotherm model, further supporting the chemical control theory for a multilayer system. Maximum adsorption capacity was 126 mg/g for acetaminophen removal, 40 mg/g for carbamazepine and 83 mg/g for 3,4-dichloroaniline. The biochar demonstrated good removal efficiency against all target species, showing potential as an adsorbent for water remediation.